Penggunaan media belajar untuk mengenalkan anak TK kosakata - Halfiza Etri; Rismareni Pransiska (Aṭfāluna: Journal of Islamic Early Childhood Education, 2021)
The purpose of this study was to determine the use of learning media in introducing children’s English vocabulary in Aisyiyah Kindergarten Bustanul Athfal Tapan, Pesisir Selatan District. The method used in this research is descriptive qualitative. The informants in this study were teachers who pursued classes B1, B2, B3, and B4. This study’s data collection techniques were carried out by observation, interviews, field notes, and documentation. This research was carried out for approximately five weeks. Data analysis in the form of descriptions was in the form of words with data reduction techniques, display data and drawing conclusions and data validity techniques using credibility, transferability, and dependability techniques. Based on the research results that have been done, it was found that the learning media was favored by children in the learning process of introducing children’s English vocabulary. The learning media used by teachers have various unique variations that attract children’s attention and make children more enthusiastic in learning English vocabulary introduction. The learning media used by the teacher in introducing children’s English vocabulary at Aisyiyah Bustanul Athfal Tapan Kindergarten are visual learning media in the form of flashcards, audio-visual learning media in the form of videos, and audio learning media in the form of songs.